(untitled) (Eurasian Journal of Engineering and Technology, 2022)
One of the most pressing topics in engineering right now is the work done to prevent the reliability of the machine from being eaten during operation. For efficient and long-term use of automobiles and tractors, it is necessary to know the structure of them, to make adjustments to details, spare parts and timely maintenance of the urgent problems of lubrication and cooling systems. It is necessary to choose the right lubricants and replace the lubricants in a timely manner. Machine details should be provided daily, seasonal maintenance and maintenance-1 (maintenance-1) and maintenance-2 (maintenance-2) on time. The internal combustion engine cooling system must be properly selected and the antifiris replaced.